Experimental Study on the Damage and Deterioration Behaviour of Deep Soft Rock under Water-Rock Interaction - Zenghui Zhao; Hao Liu; Xianzhou Lyu; Lei Wang; Zhongxi Tian; Jiecheng Sun (Geofluids)
The ageing disintegration, the damage, and failure mechanism of water-saturated soft rock are of significance to hazard prevention for deep mining. In this paper, indoor experiments, including disintegration behaviour tests in water, uniaxial compression failure tests of rock samples with different water contents, and variations in the microstructure of mudstone under saturated water contents, were conducted. The investigation results show that the saturated water content of mudstone is 16.96% and that the rock mass bursts completely after being immersed in water for 72 h. With increasing water content, the uniaxial strength and elastic modulus at the prepeak stage present significant attenuation. However, Poisson’s ratio varies little, which indicates that the swelling of cemented mudstone is not obvious when meeting water. In addition, the failure pattern of mudstone changes from overall splitting failure to block fragmentation failure. Due to ion-exchange adsorption and the wedging action of water molecules, the edge of contact between particles changes from staggered to smooth, which leads to the expansion of pores, the loosening of mudstone structures, and a decrease in mechanical strength. Therefore, the diffusion, migration, and particle expansion of illite and other clay minerals in mudstone are the main factors leading to the structural damage and strength reduction of weakly cemented rock under water-rock interactions.